Evolving trends in strabismus following retinal surgery: is there still a role for botulinum toxin?. (2nd April 2020) - Moorthy, S.; Theodorou, M.; Hancox, J.; Adams, G. G.
ABSTRACT: Purpose: Ocular motility disturbances following retinal detachment surgery are well documented, resulting in ocular misalignment and disabling diplopia. Interestingly, there has been a downward trend over the last decade across the United Kingdom with the evolution of refined vitrectomy techniques and instrumentation. We aim to report our updated experience on factors influencing botulinum toxin outcomes in view of the trend toward vitrectomy. Methods: The Moorfields strabismus service carried out a follow-up retrospective study of all subjects that received botulinum toxin for retinal surgery-related strabismus at our center over an eleven-year period. All new onset constant or intermittent strabismus following retinal detachment surgery were included. Botulinum toxin response was stratified to good and poor. Results: 32 patients fulfilled our criteria, with a mean follow-up of 20 months. The majority were vitrectomised eyes (62%), presented with diplopia (60%) and exotropia (66%). All isolated and combined vertical deviations (18%) were noted among cryobuckled eyes only. Baseline largest mean horizontal deviation was 49 and 51 prism diopters (PD) among the good and poor responders, respectively. A statistically and clinically significant reduction in the horizontal angle of deviation was noted among the good ( p < .0001) responders, requiring a mean of six injections, in comparison to the poor responders ( p = .03). Of the good responders, five patients (16%) with decompensated phorias regained fusion control. A small number of complications (15%) were noted, the most marked being intractable diplopia in a good responder (3%) with failure to fuse. Conclusions: Botulinum toxin is a useful treatment modality, particularly when surgical options are limited. It can restore binocularity in patients with preexisting fusion potential. Ocular cosmesis can be achieved but requires ongoing injections. Barriers to fusion restoration include multiple retinal surgeries, persistent macula pathology and central-peripheral retinal rivalry. This highlights the need for rigorous baseline macula assessment to allow a tailored approach when considering botulinum toxin therapy for strabismus.